Application of Game-Based Learning to Improve Islamic Religious Education Learning Outcomes on the Material of Gunnah Reading Rules and Tajweed at State Junior High School 10 Merangin - Dini Adelia; Yulia Oktarina (Lembaga Bale Literasi, 2026)
This study aimed to improve students' learning outcomes in Islamic Religious Education (PAI), particularly on the topic of the rules of reading Ghunnah and Tajweed, through the implementation of the Game-Based Learning method. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles. The participants were 30 seventh-grade students of SMP Negeri 10 Merangin. The intervention involved educational games, including quiz-based and collaborative learning activities, designed to increase students' engagement and understanding of the learning material. Data were collected through learning achievement tests and classroom observations. The validity of the data was ensured through expert validation of the research instruments and triangulation of observation and test data. Data were analyzed using descriptive quantitative techniques. Classical learning mastery was defined as at least 85% of students achieving the Minimum Mastery Criterion (KKTP) of 76. The findings revealed that the implementation of Game-Based Learning significantly improved students' participation and learning outcomes. Classical learning mastery increased from 40.0% in the pre-cycle to 63.3% in Cycle I and 86.7% in Cycle II, indicating that the success criterion had been achieved. These findings suggest that Game-Based Learning is an effective instructional approach for creating an interactive learning environment and improving students' understanding of the concepts of Ghunnah and Tajweed.